Effects of a novel mesoionic insecticide, triflumezopyrim, on the feeding behavior of rice planthoppers, Nilaparvata lugens and Sogatella furcifera (Hemiptera: Delphacidae) - Jun ZHU; Wen-qing SUN; Yao LI; Lin-quan GE; Guo-qing YANG; Jian-xiang XU; Fang LIU (Journal of Integrative Agriculture, 2020)
The rice planthoppers, Nilaparvata lugens and Sogatella furcifera, are important sap-sucking pests of rice in Asia. The mesoionic insecticide triflumezopyrim was previously shown to be highly effective in controlling both N. lugens and S. furcifera. In this study, electropenetrography (EPG) was used to evaluate the effect of three triflumezopyrim concentrations (LC10, LC50 and LC90) on the feeding behavior of N. lugens and S. furcifera. EPG signals of planthoppes indicated that there were six different waveforms NP, N1, N2, N3, N4, and N5, which corresponded to non-penetration, stylet penetration into epidermis, salivation, extracellular movement of stylet, sap ingestion in phloem, and water ingestion in xylem during feeding. Compared to untreated controls, triflumezopyrim at LC50 and LC90 prolonged the duration of the non-penetration period by 105.3 to 333.7%. The probing frequencies of N. lugens exposed to triflumezopyrim at LC10 and LC50 were significantly increased; however, the probing frequencies of S. furcifera showed a significant decrease when exposed to triflumezopyrim at all concentrations. Triflumezopyrim exposure prolonged the duration of salivation and shortened the duration of extracellular movement. The duration of phloem sap ingestion decreased from 37.2 to 77.7% in the LC50 and LC90 treatments, respectively. Differences in feeding behavior in response to triflumezopyrim and pymetrozine were minimal. In summary, the results show that the LC50 and LC90 concentrations of triflumezopyrim inhibit the feeding activities of N. lugens and S. furcifera mainly by prolonging the duration of non-penetration and by shortening the duration of phloem sap ingestion, which may foster more efficient use of triflumezopyrim in Asia.